Relations industrielles / Industrial Relations (1946)
Relations industrielles/Industrial Relations (RI/IR) is a bilingual quarterly published since 1945 by the Department of Industrial Relations at Laval University (Québec, Canada). It was the world's first academic journal in industrial relations and is the only journal in the field in Canada.